Case Report: Aicardi-Goutières Syndrome Type 6 and Dyschromatosis Symmetrica Hereditaria With Congenital Heart Disease and Mitral Valve Calcification – Phenotypic Variants Caused by Adenosine Deaminase Acting on the RNA 1 Gene Homozygous Mutations - Liu, Lingjuan; Zhang, Lu; Huang, Peng; Xiong, Jie; Xiao, Yangyang; Wang, Cheng; Mao, Dingan; Liu, Liqun (Frontiers in Pediatrics, 2022)
Dyschromatosis symmetrica hereditaria (DSH), characterized by a mixture of hyper- and hypopigmented macules on the skin, is a rare pigmentary dermatosis of autosomal dominant inheritance. The pathogenic gene is adenosine deaminase acting on the RNA 1 gene (ADAR1), mutations in this gene also lead to Aicardi-Goutières syndrome type 6 (AGS 6), a rare hereditary encephalopathy with isolated spastic paraplegia. The pathomechanism of the ADAR1 gene mutations inducing DSH has not been clarified yet. We report the first case of DSH combined with ASG caused by the homozygous mutation of the ADAR1 gene in China (c.1622T > A) and reviewed the relevant literature. AGS 6 could occur in both men and women, and start in infancy. The main characteristics are growth retardation, skin depigmentation, intracranial calcification, and cerebral white matter lesions. In the current paper, the proband also had patent ductus arteriosus (PDA), ventricular septal defect (VSD), and mitral valve calcification, which are new symptoms that have not been reported in other cases. Additionally, we also aim to discuss the possible molecular mechanisms underlying the clinical heterogeneity caused by ADAR1 gene mutations.